How might Gyrodactylus parasitism modify trade-offs between female preference and susceptibility of males to predation in Trinidadian guppies?. Issue 7 (June 2022) - Heckley, Alexis M.; de Lira, José Jonathas P.R.; Hendry, Andrew P.; Pérez-Jvostov, Felipe
Graphical abstract: Highlights: Male guppies infected with Gyrodactylus parasites are less preferred by females. Male guppies preferred by females are not more likely to be eaten by predators. Parasitism could confound trade-offs between female preference and predation risk. Abstract: A number of examples exist of trade-offs between mating success and survival; that is, success in one fitness component comes at the cost of success in the other fitness component. However, these expected trade-offs are – perhaps even more commonly – not observed. One explanation for this apparent paradox of missing trade-offs could be that the other factors generating fitness variation across individuals confound or obscure the expected trade-off. These confounding effects could arise in two general ways: (i) the additional source of variation could positively (or negatively) influence both fitness components ("shared confounder" hypothesis), or (ii) the additional source of variation could influence only one fitness component ("non-shared confounder" hypothesis). We tested whether parasitism by Gyrodactylus spp. could be a confounder of trade-offs between female preference and susceptibility to predation for male Trinidadian guppies ( Poecilia reticulata ). As in previous work, we did not find the expected trade-off; that is, the males preferred by females were not more likely to be eaten by predators. Because half of the experimental males were infected by Gyrodactylus in a paired design, we were able to show that females discriminated against infected males, but that infected males were not more susceptible to predation. Our results thus provide support for the non-shared confounder hypothesis. That is, by negatively affecting one fitness component (female choice) but not the other (susceptibility to predation), parasitism by Gyrodactylus could obscure the expected trade-off between female preference and susceptibility to predation.